Genomic analysis of the evolution of phototrophy among haloalkaliphilic Rhodobacterales. - Kopejtka, Karel (Jihočeská univerzita, 2019)
This RNDr. thesis presents results of a research focussed on the evolution of phototrophy in the bacterial order Rhodobacterales. Genomes of three closely related haloalkaliphilic representatives, differing in their phototrophic capacity and oxygen preference, were sequenced. A comparative genomic analysis revealed close homology of photosynthetic proteins and similarity in photosynthesis gene organization among the studied phototrophic species. The main conclusion of the thesis is that the last common ancestor of all haloalkaliphilic members of the Rhodobacter-Rhodobaca group inside the Rhodobacterales clade was phototrophic
Genomic analysis of the evolution of phototrophy among haloalkaliphilic Rhodobacterales.
Keywords: Anoxygenic photosynthesis; bacteriochlorophyll; horizontal gene transfer; photosynthesis gene cluster; Rhodobacteraceae.